THE ROLE OF EMOTIONAL INTELLIGENCE IN MODERATING THE RELATIONSHIP BETWEEN PERCEIVED INTERPARENTAL CONFLICT AND MARITAL SATISFACTION AMONG MARRIED INDIVIDUALS: Menjaga Keharmonisan Keluarga: Peran Kecerdasan Emosional dalam Memoderasi Hubungan antara Persepsi Konflik Orang Tua dan Kepuasan Pernikahan - Rahelda Defanti; Lathifah Hanum; Cantyo A. Dannisworo; Fivi Nurwianti (Faculty of Social Science and Human Ecology, IPB University, 2025)
The experience of growing up in a conflict-ridden family significantly influences individuals' views on marriage, emotion regulation, and the development of certain relationship patterns, which may either reflect or deviate from their parents' conflict-handling behaviors. This study examines the role of emotional intelligence in moderating the relationship between perceived parental conflict and marital satisfaction. This correlational quantitative study included 346 married men and women (M = 30.7, SD = 5.77), selected through purposive sampling. Marital satisfaction was measured using the Couple Satisfaction Index-16 (CSI-16), perceived parental conflict with the PIC-I/F, and emotional intelligence with the Trait Emotional Intelligence Questionnaire Short Form (TEIQUE-SF). Data were analyzed using simple moderation techniques with the PROCESS model. Results showed a significant negative correlation between individual perceptions of parental conflict and marital satisfaction. However, emotional intelligence did not moderate this relationship. This suggests that even individuals with high emotional intelligence continue to experience the negative impact of perceived parental conflict on marital satisfaction, with no significant reduction in its effect.